The Principle Of Continuity At Secondary School - Ziyoda Ibrakhimovna Umarova (Euro Asian Journal Publishing, 2024)
The principle of continuity in secondary education focuses on ensuring a smooth transition in students' learning experiences as they progress through their academic journey. This principle highlights the need to build on what students already know, creating a cohesive learning environment that nurtures their development. This paper explores the theoretical basis of continuity in education, its practical applications in curriculum design, and its effects on student engagement and achievement. By examining specific case studies and teaching methods, the study emphasizes how continuity fosters a deeper understanding of subjects, encourages lifelong learning, and prepares students for future challenges. The findings indicate that incorporating the principle of continuity into secondary education can improve educational outcomes and better prepare students for success in post-secondary education.
Keywords: continuity; secondary education; curriculum design; knowledge retention